2020
DOI: 10.5093/pi2020a17
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Transformational Leadership on Volunteers’ Intention to Remain at Non-profit Organizations

Abstract: According to Penner (2002, p. 448), volunteerism can be defined as long-term planned prosocial behaviors that benefit strangers and occur within an organizational setting. Volunteers are an enormous resource for non-profit organizations operating in different fields, such as health, education, community services, churches, and sports (Vecina et al., 2013). In 2018, around 77.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 59 publications
(72 reference statements)
3
15
0
Order By: Relevance
“…Self-efficacy was found to partially and significantly mediate this relationship. The study by Almas et al (2020) on the relationship between transformational leadership and retention of volunteering employees in non-profit organizations in Spain yielded similar results to the study by Judeh and Abou-moghli (2019), revealing a positive significant relationship between the two variables. Satisfaction was found to partially mediate this relationship through organizational commitment and role loyalty.…”
Section: Transformational Leadership and Staff Retentionsupporting
confidence: 78%
“…Self-efficacy was found to partially and significantly mediate this relationship. The study by Almas et al (2020) on the relationship between transformational leadership and retention of volunteering employees in non-profit organizations in Spain yielded similar results to the study by Judeh and Abou-moghli (2019), revealing a positive significant relationship between the two variables. Satisfaction was found to partially mediate this relationship through organizational commitment and role loyalty.…”
Section: Transformational Leadership and Staff Retentionsupporting
confidence: 78%
“…In addition, TPB is used to study the willingness of volunteers to stay on and predict the possibility of participation in future volunteer activities. Several studies have provided reasonable answers to volunteers' lasting motivation from the perspective of TPB (White et al, 2017;Almas et al, 2020).…”
Section: Co-occurrence Analysis On Abstractmentioning
confidence: 99%
“…Among the motivations of Chinese volunteers, collectivism seems to be dominant (Wang and Wu, 2014;Guo et al, 2021); because of cultural differences, American volunteers are attentive to the motivation factors of collectivism, but also focus on individualism (Mencken and Fitz, 2013;Cnaan et al, 2017;Yamashita et al, 2019) (Dwyer et al, 2013;Güntert and Wehner, 2015) while citing psychological journals provides evidence for scale design (Bang et al, 2019). ( 5) The co-occurrence analysis and cluster analysis of keywords reveal that self-determination theory (Finkelstein, 2009;Güntert and Wehner, 2015;Van Schie et al, 2015) and the theory of planned behavior (Warburton and Terry, 2000;Greenslade and White, 2005;Hyde and Knowles, 2013;White et al, 2017;Almas et al, 2020) are the two most frequently applied. An evolution analysis revealed that a mature research system has been developed in this field.…”
Section: Conclusion Implications and Prospect Conclusionmentioning
confidence: 99%
“…Volunteers are an enormous resource for non-profit organizations operating in different fields, such as health, education, community services, churches, and sports (Almas et al, 2020). This study refers to volunteers funded by federal agencies as stipendpaid volunteers or stipend volunteers.…”
Section: Volunteers and Organizational Commitmentmentioning
confidence: 99%